Prediction of labour outcomes using prelabour computerised cardiotocogram and maternal and fetal Doppler indices: A prospective cohort study - Moungmaithong S. (2023)
Objectives: To investigate the association and the potential value of prelabour fetal heart rate short-term variability (STV) determined by computerised cardiotocography (cCTG) and maternal and fetal Doppler in predicting labour outcomes. Design: Prospective cohort study. Setting: The Prince of Wales Hospital, a tertiary maternity unit, in Hong Kong SAR. Population: Women with a term singleton pregnancy in latent phase of labour or before labour induction were recruited during May 2019–November 2021. Methods: Prelabour ultrasonographic assessment of fetal growth, Doppler velocimetry and prelabour cCTG monitoring including Dawes–Redman CTG analysis were registered shortly before induction of labour or during the latent phase of spontaneous labour. Main outcome measures: Umbilical cord arterial pH, emergency delivery due to pathological CTG during labour and neonatal intensive care unit (NICU)/special care baby unit (SCBU) admission. Results: Of the 470 pregnant women invited to participate in the study, 440 women provided informed consent and a total of 400 participants were included for further analysis. Thirty-four (8.5%) participants underwent emergency delivery for pathological CTG during labour. A total of 6 (1.50%) and 148 (37.00%) newborns required NICU and SCBU admission, respectively. Middle cerebral artery pulsatility index (MCA-PI) and MCA-PI z-score were significantly lower in pregnancies that required emergency delivery for pathological CTG during labour compared with those that did not (1.23 [1.07–1.40] versus 1.40 [1.22–1.64], p = 0.002; and 0.55 ± 1.07 vs. 0.12 ± 1.06), p = 0.049]. This study demonstrated a weakly positive correlation between umbilical cord arterial pH and prelabour log10 STV (r = 0.107, p = 0.035) and the regression analyses revealed that the contributing factors for umbilical cord arterial pH were smoking (p = 0.006) and prelabour log10 STV (p = 0.025). Conclusions: In pregnant women admitted in latent phase of labour or for induction of labour at term, prelabour cCTG STV had a weakly positive association with umbilical cord arterial pH but was not predictive of emergency delivery due to pathological CTG during labour.